State-space Modelling and Digital Controller Design for DC-DC Converter - Oladimeji Ibrahim; Nor Zaihar Yahaya; Nordin Saad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The recent development in digital technology offers better platform for easy implementation of advance control algorithm in power converter design making digital control a viable alternative to analogue counterpart. Controller design for power converters has been very challenging due to non-linear characteristics of power switches, the supply voltage variability, load current changes and circuit element variation. This paper presents dynamic averaged state-space modelling of non-ideal dc-dc boost converter with parasitic and digital controller design for boost converter using digital redesign and direct digital design methods. The system was simulated in Matlab/Simulink to investigate the dynamic performance of the two controllers’ transient response, control bandwidth and response to variable supply voltage. The results demonstrated fast transient and wide control bandwidth for tight voltage regulation of variable input voltage.